Prevalence, Antibiotic Susceptibility, and Molecular Characterization of Cronobacter spp. Isolated From Edible Mushrooms in China - Li, Chengsi; Zeng, Haiyan; Zhang, Jumei; He, Wenjing; Ling, Na; Chen, Moutong; Wu, Shi; Lei, Tao; Wu, Haoming; Ye, Yingwang; Ding, Yu; Wang, Juan; et al. (Frontiers in Microbiology, 2019)
Cronobacter spp. are foodborne pathogens that can infect and cause life-threatening diseases in all age groups, particularly in infants and immunocompromised elderly. This study aimed to investigate the prevalence, antibiotic susceptibility and molecular characteristics of Cronobacter spp. isolates in edible mushrooms collected from 44 cities in China. In total, 668 edible mushrooms were collected from traditional retail markets and supermarkets and were analyzed by quantitative methods, PCR-based serotyping, multilocus sequence typing (MLST), and antibiotic susceptibility testing. Among the 668 samples tested, 89 (13.32%) were positive for Cronobacter spp., and the contamination levels exceeded the 110 most probable number (MPN)/g in 13.48% (12/89) of the samples. Flammulina velutipes samples had the highest contamination rate of 17.54% (37/211), whereas Hypsizygus marmoreus samples had the lowest contamination rate of 3.28% (2/61). Ten serotypes were identified among 115 isolates, of which the C. sakazakii serogroup O1 (n = 32) was the primary serotype. MLST indicated that there was quite high genetic diversity in Cronobacter spp. and 72 sequence types were identified, 17 of which were new. Notably, C. sakazakii ST148 (n = 10) was the most prevalent, followed by C. malonaticus ST7 (n = 5). Antibiotic susceptibility testing revealed that the majority of Cronobacter strains were susceptible to the 16 antibiotics tested. However, a portion of isolates exhibited relatively high resistance to cephalothin, with resistance and intermediate rates of 93.91% and 6.09%, respectively. One isolate (cro300A) was multidrug-resistant, with resistance to five antibiotics. Overall, this large-scale study revealed the relatively high prevalence and high genetic diversity of Cronobacter spp. on edible mushrooms in China, indicating a potential public health concern. To our knowledge, this is the first large-scale and systematic study on the prevalence of Cronobacter spp. on edible mushrooms in China, and the findings can provide valuable information that can guide the establishment of effective measures for the control and precaution of Cronobacter on edible mushrooms during production processes.